Status of child population health - the future of the country (part 1) - Yu.G. Antipkin; О.P. Volosovets; V.G. Maidannik; V.S. Berezenko; R.О. Moiseenko; O.V. Vygovska; S.P. Krivopustov; V.N. Zabolotko; M.L. Aryaev; O.E. Abaturov; T.O. Kryuchko; G.V. Beketova; et al. (Zaslavsky O.Yu., 2018)
The article of the team of scientists of pediatricians and organizers of pediatric health care of Ukraine is devoted to the study of the main trends in the health status of children over last 22 years. The results of the analysis of the incidence and prevalence of diseases among Ukrainian child population, infant mortality rates over the past two decades demonstrates that they remain significantly higher than the average European indicators against the background of a progressive decrease in the number of child population at 3,16 million people. The prevalence of childhood diseases in Ukraine over past 22 years has grown by 41 %, the incidence of childhood diseases arose by 36 %. The article considers the ways of solving a number of new social and medico-ecological problems that negatively affect child health.